Holler [videorecording (DVD)] - Riegel, Nicole; Riegel, Nicole; Barden, Jessica, 1992-; Halper, Gus; Amelio, Austin (RLJE Films, 2021)
When a teenage girl living in a small town in Ohio with limited opportunities and closing factories is accepted to college, she tries to earn money by working with her older brother in scrap metal, but soon becomes involved in stealing metal.